Development of ecological tourism based on the elaborated tourist route - Ya. A. Kulikova; A. Yu. Shevyakov; I. A. Kuznetsov (Вестник Северо-Кавказского федерального университета)
The article discusses the peculiarities of the development of ecological tourism in Russia. The main goal is to identify the problems and prospects for the development of ecological tourism in the Tambov region on the basis of the elaborated ecological tourist route. The authors identified several available methods that were used in the study. The article analyzes the current state and mechanisms of state regulation of ecological tourism in the Tambov region, the possibilities and prospects for the development of ecological tourism in the Tambov region. An ecological tourist route has been elaborated for regional tourism enterprises in order to develop ecological tourism in the region.